Ameliorative effect of Lactobacillus plantarum WW-fermented soy extract on rat fatty liver via the PPAR signaling pathway. (September 2019) - Cao, Chengxu; Wu, Rina; Zhu, Xinyuan; Li, Yang; Li, Mo; An, Feiyu; Wu, Junrui
Graphical abstract: Highlights: Lactobacillus plantarum WW fermented-soy-extract (FSE) attenuated high-fat-diet (HFD)-induced lipid metabolism dysfunction. We demonstrate liver transcriptome profiles in HFD and HFD + FSE. In this study, we focused on pathways related to lipid signaling. Our observations improve understanding of the mechanisms by which FSE relieves hyperlipidemia. Abstract: The effects of soy extract fermented by Lactobacillus plantarum WW ( L. plantarum WW) on high fat diet (HFD)-induced hyperlipidemia and liver injury were examined. Sprague-Dawley rats were randomly divided into normal chow (C), HFD and HFD +  L. plantarum WW-fermented soy extract (HFD + FSE). We found that L. plantarum WW-FSE treatment significantly restored changes to body weight and pathological indices caused by fatty liver disease. RNA-seq analysis showed that treatment with L. plantarum WW-FSE altered expression of genes involved in lipid metabolism, and in oxidation-reduction processes. This study supported that the peroxisome proliferator-activated receptor (PPAR) signaling pathway may be involved in lipid metabolism, and suggested that dietary L. plantarum WW-FSE ameliorates HFD-induced lipid metabolism disturbance in rat liver associated with PPAR signaling pathway. These observations shed new light on possible treatment of hyperlipidemia.